Inside Cover: Exploring the Vibrational Side of Spin‐Phonon Coupling in Single‐Molecule Magnets via 161Dy Nuclear Resonance Vibrational Spectroscopy (Angew. Chem. Int. Ed. 23/2020). Issue 23 (28th April 2020) - Scherthan, Lena; Pfleger, Rouven F.; Auerbach, Hendrik; Hochdörffer, Tim; Wolny, Juliusz A.; Bi, Wenli; Zhao, Jiyong; Hu, Michael Y.; Alp, E. Ercan; Anson, Christopher E.; Diller, Rolf; Powell, Annie K.; et al.
Abstract : Hematite‐based mesocrystals assembled from highly oriented tiny nanoparticle subunits achieve superior photoelectrochemical water splitting performance under solar irradiation. In their Research Article on page 9047, T. Tachikawa and co‐workers show how rich interfacial oxygen vacancies yield an exceedingly high carrier density and a large proportion of ultra‐narrow depletion layers (<1 nm) inside the mesoporous film, thus boosting multihole water oxidation with a very low activation energy.